Influencing Factors of Urban Residents' Garbage Classification and Recycling Behavior Driving Mechanism in Artificial Intelligence Environment - Gan, Baiqiang; Zhang, Chi (IOP conference series. Earth and environmental science, 2020)
With the rapid development of urbanization, urban domestic waste is also increasing, if the garbage cannot be effectively classified, there will be a dilemma of garbage siege. In recent years, artificial intelligence technology has been applied in the field of garbage classification, which provides a convenient means for garbage classification. However, technological innovation can only alleviate the accumulated total amount of garbage, and finding the source of garbage generation is the key to solve the problem. Therefore, based on the theory of planned behavior, A-B-C theory and interpersonal behavior theory, from the policy level, the social level and the individual level, this paper puts forward some suggestions, it is composed of government, society, individual and other organizations, and puts forward the corresponding research hypotheses. Through interviewing and questionnaire survey in Guangzhou, the sample data are collected, and then regression analysis and structural equation model analysis are used to obtain the influence degree value of residents' attitude towards garbage classification, subjective norms, perceived behavior control, situational factors, and government legal regulation on residents' living garbage classification willingness. The results show that residents' attitude towards domestic waste classification is significant and the government's legal control factors are the key factors affecting the residents' willingness of garbage classification.